Stable Schizophrenia Patients Learn Equally Well as Age-Matched Controls and Better than Elderly Controls in Two Sensorimotor Rotary Pursuit Tasks - De Picker, Livia J.; Cornelis, Claudia; Hulstijn, Wouter; Dumont, Glenn; Fransen, Erik; Timmers, Maarten; Janssens, Luc; Morrens, Manuel; Sabbe, Bernard G. C. (Frontiers in Psychiatry, 2014)
Objective: To compare sensorimotor performance and learning in stable schizophrenia patients, healthy age- and sex-matched controls and elderly controls on two variations of the Rotary Pursuit: Circle Pursuit (true motor learning) and Figure Pursuit (motor and sequence learning). Method: In the Circle Pursuit a target circle, rotating with increasing speed along a predictable circular path on the computer screen, must be followed by a cursor controlled by a pen on a writing tablet. In the eight-trial Figure Pursuit, subjects learn to draw a complex figure by pursuing the target circle that moves along an invisible trajectory between and around several goals. Tasks were administered thrice (day 1, day 2, day 7) to 30 patients with stable schizophrenia (S), 30 healthy age- and sex-matched controls (C) and 30 elderly participants (>65y; E) and recorded with a digitizing tablet and pressure-sensitive pen. The outcome measure accuracy (% of time that cursor is within the target) was used to assess performance. Results: We observed significant group differences in accuracy, both in Circle and Figure Pursuit tasks (E<S<C, p<0.01). Strong learning effects were found in each group. Learning curves were similar in Circle Pursuit but differed between groups in Figure Pursuit. When corrected for group differences in starting level, the learning gains over the three sessions of schizophrenia patients and age-matched controls were equal and both were larger than those of the elderly controls. Conclusion: Despite the reduced sensorimotor performance that was found in the schizophrenia patients their sensorimotor learning seems to be preserved. The relevance of this finding for the evaluation of procedural learning in schizophrenia is discussed. The better performance and learning rate of the patients compared to the elderly controls was unexpected and deserves further study.